2009
DOI: 10.1111/j.1399-6576.2009.01971.x
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of cardiac events in high‐risk patients undergoing emergency surgery

Abstract: Background: The aim of this study was to determine the incidence of myocardial damage and left ventricular myocardial dysfunction and their influence on outcome in high-risk patients undergoing non-elective surgery. Methods: In this prospective observational study, 211 patients with American Society of Anesthesiologists classification III or IV undergoing emergent or urgent surgery were included.Troponin I (TnI) was measured pre-operatively, 12 and 48 h post-operatively. Pre-operative N-terminal fragment of B-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
47
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 38 publications
(49 citation statements)
references
References 23 publications
2
47
0
Order By: Relevance
“…1,6,7,9,[12][13][14][15][16][17][18] The characteristics of the included studies are shown in Table I. From the 11 included studies, five were prospective.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…1,6,7,9,[12][13][14][15][16][17][18] The characteristics of the included studies are shown in Table I. From the 11 included studies, five were prospective.…”
Section: Resultsmentioning
confidence: 99%
“…From the 11 included studies, five were prospective. 1,12,13,15,17 These studies recruited patients from a variety of surgical disciplines, and included both elective and emergency patients.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations